Tetanus Case Needing Mechanical Ventilation - Demirel, İsmail; Üstün, Suzan; Üstün, Cemal (Fırat University, 2012)
Tetanus is an infection disease caused by Clostridium tetani with high mortality in which tonic muscle spasms are existed. A 60-year-old male patient had a trauma on his right foot ten days ago. His general condition was middle, conscious, cooperated, oriented enough and he had trismus and risus sardonicus. His pupils were isochoric, myotic, respiration was tachypneic (25/min), fever was 36.2oC, and he was tachycardic (128/min). He was intubated once his tachypnea increased, and mechanical ventilation was started. The case was scored as Ablett Grade III. Tracheostomy was opened in his seventh day after admitted intensive care unit. Weaning procedure was started to him when he was stable for respiratory and hemodynamically in twenty sixth day and discharged from intensive care unit to service in thirty second day. Preventing of complications and autonomic dysfunction, and controlling of muscular rigidity and spasms are general major therapeutic approaches in patients who are left over in intensive care unit. Also, we think that using of Bispectral index (BIS) will be effective for the therapeutic approachs to determining level of sedation.

Tetanoz, Clostridium tetani'nin toksini ile oluşan, tonik kas spazmlarıyla seyreden, mortalitesi yüksek bir infeksiyon hastalığıdır. Altmış yaşında erkek hastanın, 10 gün önce sağ ayağı paslı çivi ile yaralanmış. Genel durum orta, bilinç açık, koopere ve oriante olan hastanın çenesinde kilitlenme ve risus sardonicus gözlendi. Pupiller izokorik ve miyotik, solunum takipneik (25/dak), ateş 36,2oC ve taşikardik idi (128/dak). Takipnesi artan olguya endotrakeal entübasyon uygulanarak mekanik ventilasyona başlandı. Bu haliyle olgu Ablett sınıflaması Grade III olarak değerlendirildi. Yoğun bakıma yatırılan olguya yedinci günde trakeostomi açıldı. Yirmi altıncı günde solunum ve hemodinamik olarak stabil olan hastada weaning işlemine başlanarak otuz ikinci günde servise devredildi. Uzamış yoğun bakım hastalarındaki komplikasyonların ve otonomik disfonksiyonların önlenmesi, musküler rijidite ve spazmın kontrolu genel major terapötik yaklaşımlardır. Ayrıca sedasyon düzeyinin belirlenmesinde Bispectral index (BIS)'in kullanılmasının terapötik yaklaşımlar açısından faydalı olacağı düşünüldü.
Mekanik Ventilasyona Gereksinim Gösteren Tetanoz Olgusu